Religious Coping of Selected Filipino Catholic Youth - Castillo, Fides A. del ca. 20./21. Jh. (Religions, 2020)
This study determined the reliability and validity of the Brief Religious Coping Scale (Brief RCOPE) outside the Western Christian context. After construct and measurement equivalence, the Brief RCOPE was used to ascertain and illuminate the religious coping of selected Catholic youth in the Philippines. A group of students studying in Catholic universities (n = 335) completed the research measures. The findings of this study showed that the Brief RCOPE has good internal consistency and construct validity. However, the scale has two orthogonal factors. The results indicated that many Filipino Catholic youth used positive religious coping methods more frequently than negative strategies. In addition, the results suggest that Brief RCOPE may be useful to researchers interested in the religious coping of youth.